Undang-undang Islam dalam perlembagaan Malaysia: Kewajarannya berdasarkan faktor sejarah perundangan Tanah Melayu - Megat Latif, Hairuddin (Universiti Utara Malaysia, 2009)
The presence of Islam in Tanah Melayu was not an event that striked in a short and brief period.It re presented a very long historical record that took almost six hundred years.The acceptance of Islam among the Malays was realized by the adoption of Islamic legislation as the state legislation such as that of Melaka before its destruction by the Portuguese, State of Perak, State of Pahang, State of Johor, and State of Kedah prior to the British colonization.We might have often heard of the existence of Code of Law in Malacca, Law 99 of the State of Perak, Law 12 of the State of Perak, Law of Pahang, Al-Ahkam Alahdaliyyat and Tembera Datuk Paduka Tuan.All of these laws were based on syara’ law and Malay traditions.This article showed that we must oppose Hooke’s argument that said “laws used by the Muslims was a”self-law”, that is, the law that was used on the basis of obedience to religion and matters that have religious aspects.”This article also proved that the decision of Reid Commission that provided special place and status to the Muslims were appropriate and accurate.In fact, the author is of the opinion that the Reid Commission should have included another clause in the Federal Constitution which pronounced Islamic Law as the highest law in the Federal Constitution and that all other laws which contradicted with the Islamic law are considered as null and void.